Gulosibacter molinativorax gen. nov., sp. nov., a molinate-degrading bacterium, and classification of ‘Brevibacterium helvolum’ DSM 20419 as Pseudoclavibacter helvolus gen. nov., sp. nov. - Manaia, Célia M. (2011)
A Gram-positive, molinate-degrading bacterium, strain ON4T (=DSM 13485T=LMG 21909T), was isolated from a mixed bacterial culture able to mineralize the herbicide molinate. The strain was strictly aerobic, oxidase- and catalase-positive and non-acid-fast, with a growth temperature of 10–41 6C. It contained the major menaquinone MK-9 and a cell-wall peptidoglycan based on D-ornithine. 16S rDNA sequence analysis revealed that the strain formed a distinct line of descent in the family Microbacteriaceae, showing the highest 16S rDNA similarity (~95 %) to members of the genus Curtobacterium and ‘Brevibacterium helvolum’ DSM 20419 (=ATCC 13715). The latter was reported to have the cell-wall peptidoglycan type B2c and the major menaquinone MK-9, which are typical of Clavibacter, but it is clearly separated from this genus at the phylogenetic level. Based on low values of 16S rDNA sequence similarity to previously described genera and their distinctive phenotypic characteristics, it is proposed that strains ON4T and ‘B. helvolum’ DSM 20419 be classified as two novel genera and species, with the respective names Gulosibacter molinativorax gen. nov., sp. nov. and Pseudoclavibater helvolus gen. nov., sp. nov.